FAKTOR YANG BERHUBUNGAN DENGAN KELUHAN NYERI PUNGGUNG BAWAH PADA NELAYAN UDANG DI BELAWAN SICANANG MEDAN BELAWAN - Perry Boy Chandra Siahaan; Putri Yunita Pane; Hamidah Rizki (Fakultas Kesehatan Masyarakat Universitas Prima Indonesia, 2021)
Occupational health is a part of public health or public health applications in a working society and community in the workplace environment, which aims to improve work productivity and the highest degree of health. Low back pain or Low Back Pain is pain that is felt in the lower back region, between the corners of the lowest ribs to the sacrum. The working conditions of shrimp fishermen in Belawan Sicanang Medan Belawan who can cause lower back pain are the focus of this study. This research use cross sectional method and Rapid Entire Body Assessment (REBA) for ergonomic assessment process. The results of this study indicate a relationship to three aspects in Shrimp Fishermen workers namely age, work attitude, and years of work. Meanwhile there are two variables that have no relationship with lower back pain, namely Body Mass Index (BMI) and smoking habits.